Efficient synthesis of Pt–Co nanowires as cathode catalysts for proton exchange membrane fuel cells. Issue 11 (10th February 2020) - Liu, Zhikun; Yin, Yanhong; Yang, Daijun; Zhang, Cunman; Ming, Pingwen; Li, Bing; Yang, Shuting
Abstract : A simple and efficient method was used to prepare highly active and durable carbon-supported ultrathin Pt–Co nanowires (NWs) as oxygen reduction reaction (ORR) catalysts for the cathode in a proton exchange membrane fuel cell (PEMFC). Abstract : A simple and efficient method was used to prepare highly active and durable carbon-supported ultrathin Pt–Co nanowires (NWs) as oxygen reduction reaction (ORR) catalysts for the cathode in a proton exchange membrane fuel cell (PEMFC). Chromium hexacarbonyl plays a significant role in making Pt and Co form an alloyed NW, which acts as both a reducing agent and a structure directing agent. The nanocrystal exhibits a uniform nanowire morphology with a diameter of 2 nm and a length of 30 nm. In half cell tests, the Pt–Co NWs/C catalyst has a mass activity of 291.4 mA mgPt −1, which is significantly better than commercial Pt/C catalysts with 85.5 mA mgPt −1 . And after the accelerated durability test (ADT), Pt–Co NWs/C shows an electrochemically active surface area (ECSA) loss of 19.1% while the loss in the commercial catalyst is 41.8%. Also, the membrane electrode assembly (MEA) was prepared using Pt–Co NWs/C as the cathode catalyst, resulting in a maximum power density of 952 mW cm −2, which is higher than that of Pt/C. These results indicate that the one-dimensional structure of the catalyst prepared herein is favorable to improve the activity and durability, and the application of the catalyst in the MEA is also realized.